Study of the Role of Productive Waqf in Improving Community Welfare: A Qualitative Study at Rohmatul Ummah Islamic Boarding School Ringinrejo, Kediri, Indonesia - Sholihah, Fefi Diniyati; Wahidatun Nafiah Al-Farda; Lala Tri Wulandari (Open Access Indonesia Journal of Social Sciences, 2024)
Productive waqf has been recognized as a potential instrument in improving community welfare. This research aims to understand in depth how productive waqf is implemented at the Rohmatul Ummah Islamic Boarding School, as well as its impact on the welfare of the surrounding community. This research uses a qualitative approach with a case study at the Rohmatul Ummah Islamic Boarding School. Data was collected through in-depth interviews with Islamic boarding school administrators, waqf nazhir, waqf beneficiaries, as well as direct observation of productive activities managed by the waqf. Data analysis was carried out thematically. The research results show that productive waqf at the Rohmatul Ummah Islamic Boarding School is managed professionally and transparently. Waqf funds are used to finance various productive activities, such as agriculture, animal husbandry and micro businesses. This activity provides direct economic benefits to beneficiaries, such as increased income, employment opportunities, and access to basic needs. Apart from that, productive waqf also provides positive social impacts, such as improving the quality of education, health and the environment. Productive waqf has a significant role in improving the welfare of the community around the Rohmatul Ummah Islamic Boarding School. This research recommends that this model of productive waqf management in Islamic boarding schools can be replicated in other places, taking into account the local social and economic context.